Pediatric Stroke in the Southern Region of Iran: A Retrospective Prognostic Cohort Study - Nemati, Hamid; Behrad, Leila; Esmaeil Zadeh, Hossein; Paktinat, Mohammad; Mahdizadegan, Nima (Iranian Journal of Child Neurology, 2023)
Objective Childhood stroke is linked to high personal costs for affected children and their families since more than half of the survivors are impaired fora long time, hampering their normal development and lifestyle. Thus, the present study aimed to evaluate the neurological developmental outcomes of children admitted to Namazi hospital, Shiraz, Iran, for ischemic and hemorrhagic stroke with a five-year follow-up. Ma a retrospective cohort study on children admitted to Namazi Hospital due to ischemic and hemorrhagic stroke during the past three years (2012-2015). The information was collected by reviewing the medical records and clinically visiting the patients on follow-up. The SPSS 21.0 software was used for statistical analysis. Materials & Method This is a retrospective cohort study on children admitted to Namazi hospital due to ischemic and hemorrhagic stroke during past three years (2012-2015). The information was collected by reviewing the medical records and clinically visiting the patients at the time of follow up. The SPSS 21.0 software was used for statistical analysis Settings. Results The patients’ mean age at the time of stroke was 6.87 ± 4.60 years. The mean follow-up period was 3.5 ± 1.64 years. 53.1% of the children (N=17) were diagnosed with hemorrhagic stroke, and 46.9% (N=15) with ischemic stroke. The most frequent symptoms first presented by the study population were a decrease in the level of consciousness (LOC) (40.6%), headaches (37.5 %), and hand/arm/leg weakness (34.4%), respectively. The number of patients in the poor and severe outcome group was 73.3% in the ischemic and 52.9% in the hemorrhagic group. Conclusion Hemorrhagic stroke was slightly more frequent than ischemic stroke, and stroke was more frequent in boys. A decrease in LOC and headaches were the most common symptoms upon admission. The left sensorimotor area was the most involved in both ischemic and hemorrhagic groups. In addition, trauma was the most common cause of stroke in this study population.